What is the driving force behind molecular triangles and their guests? A quantum chemical perspective about host–guest interactions. Issue 34 (19th August 2020) - Nagurniak, Glaucio R.; Piotrowski, Maurício J.; Muñoz-Castro, Àlvaro; Cascaldi, João B. S.; Parreira, Renato L. T.; Caramori, Giovanni F.
Abstract : The physical nature of host–guest interactions occurring between molecular triangles and linear anions was explored using DFT calculations combined with energy decomposition analyses, nuclear independent chemical shift, and non-covalent interactions. Abstract : The physical nature of host–guest (HG) interactions occurring between molecular triangles and linear anions was explored using density functional theory (DFT) calculations combined with energy decomposition analyses (EDA), nuclear independent chemical shift (NICS), and non-covalent interaction index (NCI). We demonstrate that: (i) in addition to the host being significantly rigid, the strain energies are not negligible, especially for host 2 ; (ii) halogen anions interact mainly by electrostatic forces (Δ E elst > Δ E orbtot > Δ E disp ), meanwhile; (iii) trihalogen anions interact mostly by dispersion forces (Δ E disp > Δ E elst ≈ Δ E orbtot). The NICS and NCI calculations corroborate the idea that HG interactions are considerably mediated through dispersion terms, and also indicate an antiaromatic character inside the host walls.